2019
DOI: 10.1155/2019/3567813
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Choroidal Thinning in High Myopia, Diabetes Mellitus, and Aging: A Swept-Source OCT Study

Abstract: Purpose. To compare the macular choroidal thinning between young healthy, aged healthy, young high myopic, and aged type 2 diabetic (T2D) patients using the Early Treatment Diabetic Retinopathy Study (ETDRS) grid and three-dimensional (3D) maps. Methods. A prospective study including 102 eyes of 51 healthy young subjects, 60 eyes of 30 healthy aged subjects, 24 eyes of 12 high myopic patients, and 110 eyes of 55 T2D patients. Choroidal thickness (CT) was examined with swept-source optical coherence tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…In this study, we proposed that Classifiers 1-6 can predict AXL by means of patients' age, sex, height, weight, and CT measured from OCT images. Studies have reported that CT is negatively correlated with AXL, and people with high myopia tend to have a thinner choroid (7)(8)(9)(10)(11). However, few studies have assessed the prediction of AXL by means of CT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we proposed that Classifiers 1-6 can predict AXL by means of patients' age, sex, height, weight, and CT measured from OCT images. Studies have reported that CT is negatively correlated with AXL, and people with high myopia tend to have a thinner choroid (7)(8)(9)(10)(11). However, few studies have assessed the prediction of AXL by means of CT.…”
Section: Discussionmentioning
confidence: 99%
“…Morgan et al (6) suggested that the elongated AXL is the underlying mechanism of myopia development and progression. Choroid, located at the exterior of the retina and which provides blood supply to the outer portion of the retina, has been reported to be thinner in myopic than emmetropic eyes and is related to AXL elongation (7). Choroid thinning not only correlates with myopia progression but is also related to other complications, such as staphyloma and chorioretinal atrophy in high myopia (7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Using SS-OCT, researchers found that choroidal thinning actually developed before retinal thinning occurred during myopia progression; myopia shift was found to be independently correlated with central fovea choroidal thinning and axial length [ 70 ], indicating the value of SS-OCT to clarify the critical roles of choroid and retina during myopia progression. In addition, choroidal thinning was also found to be correlated to MMD [ 71 ], and topographic variations were identified in 3D maps of choroidal thickness [ 72 ]. Another important choroidal feature is peripapillary intrachoroidal cavitation, usually located inferior to the optic nerve in highly myopic eyes [ 73 ].…”
Section: Oct and Octa For The Assessment Of Ocular Structures In Myopesmentioning
confidence: 99%
“…Based on previous studies discussed in the earlier part of this report, myopic refractive error and long AL may be protective factors against DR. Possible mechanisms might be attributable to the regulating effect of the increase in AL, posterior vitreous detachment, low blood flow perfusion in the retina, choroidal thinning, and the alteration of cytokine profile. 39; 40; 41; 42; 43; 44 While the exact mechanisms of how myopia is protective against DR remain elusive, most of the attention is placed on the pathological changes of the eyeball incurred by the increasing AL during the progression of myopia. 39; 40; 41…”
Section: Possible Mechanisms Of the Protective Effectmentioning
confidence: 99%
“…39; 40; 41; 42; 43; 44 While the exact mechanisms of how myopia is protective against DR remain elusive, most of the attention is placed on the pathological changes of the eyeball incurred by the increasing AL during the progression of myopia. 39; 40; 41…”
Section: Possible Mechanisms Of the Protective Effectmentioning
confidence: 99%